(untitled) (Bangladesh Journal of Botany, 2014)
Castor bean (Ricinus communis L.) is one of the most important non-edible oilseed crops. Characterization of seed development and lipid accumulation from female flowers pollinated to mature seeds has been carried out. The temporal expression patterns of 65 lipid genes involved in fatty acid and triacylglycerol biosynthesis using the semi-quantitative RT-PCR technique were also investigated. The 65 genes displayed diverse expression patterns which could be collectively grouped into seven groups (I - VII). Four gene groups (I, II, III and V) covering 40 lipid genes presented up-regulated expression patterns, correlating with the rapid lipid accumulation within developing seeds. The present study provides an extended glimpse of the expression patterns of lipid genes involved in fatty acid biosynthesis and triacylglycerol assembly in developing seeds of castor bean, which could serve in variety improvement of castor bean by genetic engineering approach. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19743 Bangladesh J. Bot. 43(1): 37-43, 2014 (June)